TELAAH MATA PELAJARAN PENDIDIKAN AGAMA DAN BUDI PEKERTI - Silvia Wirnanda Rambe (Jurnal Al Wahyu, 2023)
Islamic Religious Education (PAI) at the junior high school level is the part that explains the unique situation or motivation behind why this is important to study or explain. This basis understands the purpose of taking concentration points for PAI material at the junior high school level. A subject survey is a process of assessment and examination of a particular subject or educational program that is determined to understand the main parts contained therein. Subject investigation includes examining learning objectives, demonstrating material, demonstrating techniques, assessments, and various points of view related to the subject. Learning Islamic Religious Education (PAI) is a subject that focuses on teaching the teachings and values of the Islamic religion, with the aim of deepening understanding of Islam, strengthening religious beliefs, and encouraging daily practices that are in accordance with Islamic teachings. This includes an understanding of the Qur'an, hadith, Islamic history, ethics, and worship practices, as well as various aspects of the Islamic religion. Characteristics, also known as akhlak or morals, refers to good and correct behavior and character, including attitudes, values, and actions that reflect positive personality such as honesty, kindness, helpfulness, politeness, and responsibility. Character learning aims to develop positive character in students and help them interact with the environment and society well. Assessment of character learning at the secondary school level is an interaction that includes surveying and describing learning and improving student personality.